2020
DOI: 10.1186/s40623-020-01293-0
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint-based direct data assimilation of GNSS time series for optimizing frictional parameters and predicting postseismic deformation following the 2003 Tokachi-oki earthquake

Abstract: Postseismic Global Navigation Satellite System (GNSS) time series followed by megathrust earthquakes can be interpreted as a result of afterslip on the plate interface, especially in its early phase. Afterslip is a stress release process accumulated by adjacent coseismic slip and can be considered a recovery process for future events during earthquake cycles. Spatio-temporal evolution of afterslip often triggers subsequent earthquakes through stress perturbation. Therefore, it is important to quantitatively ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Therefore, for fault slip monitoring, it is vital to determine the appropriate frictional parameters by combining observations and physics‐based models. To achieve this, data assimilations have been employed to investigate frictional parameters from observed slip velocities of afterslip (Kano et al., 2015, 2020) and long‐term SSEs (Hirahara & Nishikiori, 2019). Kano et al.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, for fault slip monitoring, it is vital to determine the appropriate frictional parameters by combining observations and physics‐based models. To achieve this, data assimilations have been employed to investigate frictional parameters from observed slip velocities of afterslip (Kano et al., 2015, 2020) and long‐term SSEs (Hirahara & Nishikiori, 2019). Kano et al.…”
Section: Introductionmentioning
confidence: 99%
“…Kano et al. (2020) estimated frictional parameters from observed crustal deformation following the 2003 Tokachi‐oki earthquake and predicted subsequent fault slips and crustal deformation. These studies confirmed that data assimilations enable the optimization of unknown frictional parameters on faults based on observed crustal deformation and physics‐based models.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations